Optimisation of CNC turning parameters using RSM for inconel 718 in dry cutting conditions, focusing on surface roughness - Suhaimey, Muhammad Dzulzikri; Tamin, Norfauzi; Mohd Salleh, Kahirol; Hakimi, Ahmad Arif; Rashidi, Iqmal Farhan; Azlan, Umar Al Amani; Ab Wahab, Norfariza; Wan Abdul Malik, Wan Abdul Hafiz (UiTM Press, 2025)
Inconel 718 is widely utilised in machining applications due to its exceptional mechanical properties, particularly in high-temperature environments, making it a preferred material in industries such as aerospace and automotive. However, the machining of Inconel 718 material presents significant challenges, particularly in achieving an optimal surface finish under dry-cutting conditions using a CNC turning machine. This study addresses the critical issue of improper cutting parameters involving cutting speed (Vc) and feed rate (fz), which can adversely affect the surface quality of machined components. This research aims to determine the optimal cutting parameters that minimise surface roughness (Ra) on Inconel 718 in dry-cutting conditions. A systematic methodology was employed, wherein various Vc from 30 to 100 m/min, fz was adjusted between 0.03 to 0.07 mm/rev, and a constant depth of cut was set at 0.5 mm. The Response Surface Methodology (RSM) was utilised to analyse the effects of these parameters on Ra, allowing for the identification of optimal machining conditions. The results show that Vc 100 m/min and fz 0.0696 mm/rev significantly improve surface finish by producing the lowest Ra of 0.4416 µm, which is 51% better than Vc 65 m/min and fz 0.03 mm/rev. This study contributes to the body of knowledge on CNC turning machining of superalloys in dry-cutting conditions. It provides valuable insights for machine operators aiming to enhance machining efficiency and product quality in industrial applications.